The Effects of Diverse Exercise in Alleviating Loneliness and Social Isolation in the Elderly: A Systematic Review and Meta-Analysis (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
The Effects of Diverse Exercise in Alleviating Loneliness and Social Isolation in the Elderly: A Systematic Review and Meta-Analysis